PENANGANAN HAK PENGUNGSI OLEH INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DI INDONESIA (STUD KASUS KERJASAMA IOM DENGAN KOMUNITAS LOKAL DI PEKANBARU 2019-2021) - Tyara Syalsabila; Mhd. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The issue of refugees has become a concern for several countries, one of which is Indonesia. Indonesia in dealing with refugee cases cannot be separated from the help of international organizations, one of which is IOM, this is because Indonesia does not yet have legal regulations that discuss the status of determining refugee citizenship. In assisting Indonesia, IOM has collaborated with sub-countries, namely the area that has become refugee shelters, one of which is Pekanbaru City. This collaboration is carried out so that the community and refugees can both understand and understand the presence of refugees in their city. Data were obtained from journals, official websites, books, and interviews by state agencies dealing with refugee issues and local communities in Pekanbaru City. For analysis techniques, researchers used qualitative research with primary data converted into descriptive. The author uses the theory of International Organizations which states that in carrying out its role International Organizations must fulfill several aspects. Based on research shows that IOM in working with Indonesia seems to be grow. This can be seen from state actors and sub-countries, namely regions can also cooperate with international organizations, namely IOM, in terms of fulfilling the right to skills guidance training can be carried out, even in carrying out regional cooperation with international organizations, the regions involve the local community, so that the local community also plays a role in country perspective where the legality of this social group is recommended by the state through its local government. So that finally the segments under the state actors develop to take cooperative actions with international organizations. With this cooperation it is seen that the rights of refugees can be fulfilled. Keywords: Refugees, International Organizations, Local Communities, IOM.